Pesantren Al-Fattah: The Strugle of an Ascetic Waria to Create a Religious Space for Transgender Muslims in Indonesia - Nila Sari, Maesa; Alimi, Moh Yasir; Robinson, Kathryn (Komunitas, 2022)
This study seeks to describe the struggle of a Muslim transgender ascetic in claiming religious space for transgender in urban Indonesia by creating a pesantren (Islamic school). The study was conducted in Al-Fattah Pondok Pesantren, the only Islamic school for transgender in Indonesia. Al-Fattah is created by Bu Maryani, a transgender ascetic, who contributed her money, thought, energy and prayers for this school, to provide spiritual sanctuary for transvestites, despites her worsening economy and health. While many transvestites look for alternative religion, the experience of Al-Fattah reveal that transgender Muslims may find their religious sanctuary within traditional Islamic practices, not outside the traditional institutions. Al-Fattah transgender Islamic school reveal the power of lived religion, pesantren, and traditional forms of religious rituals to validate Queer spiritual practices. We argue that the use of the traditional forms of religious rituals enable the Muslim transgender to overcome the dilemma of fluidity-and-fixity in queer religious practices.